Equity market interactions: Exploring analysts' role performances at earnings presentations. Issue 4 (21st May 2018) - Graaf, Johan
Abstract : Purpose: The purpose of this paper is to contribute to the sociology of financial analysis by exploring how sell-side analysts enact their professional roles during public earnings presentations. It addresses the following research question: How do analysts perform their professional roles in interactions with managers, fund managers and other analysts? Design/methodology/approach: The research adopts a dramaturgical analysis of analysts' interactions with managers and fund managers. The empirical material includes 50 hours of direct observations of earnings presentations and 21 interviews with analysts, managers and other relevant actors. Findings: The findings show that analysts struggle with role conflicts because they need to satisfy the contrasting demands of managers, fund managers and colleagues. Performing the role of an expert critic mainly depends on the approval of managers; yet, analysts also find themselves in situations where they must confront the managers. To counter role conflicts and sustain their role performance, analysts also produce displays of role distance and carefully prepare to meet their audiences' expectations. To maintain the role of the expert critic, analysts depend on both those taking their advice (fund managers) and those being reviewed (managers). Originality/value: This study is one of few empirically rich investigations of analysts' activities, interactions with managers and meetings with multiple audiences. It also contributes to previous interview studies using dramaturgical analysis by offering in-depth observations of a single, distinct situated activity system.